2020
DOI: 10.1186/s13028-020-00543-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of virulence genes in Escherichia coli strains isolated from pre-weaned calves in the Republic of Korea

Abstract: Background Escherichia coli is an important cause of diarrhea in calves and its diarrheagenic properties are related to presence of certain virulence genes. In this study, the prevalence of virulence genes F5 , F17 , F41 , sta , stx1 , stx2 , eae , and saa in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 33 publications
0
9
0
2
Order By: Relevance
“…In our study, stx1, stx2, and st VGs were more frequent than eae , hly , aatA , and lt . In another report, however, stx1 and eae were found at a higher rate than st and stx2 [ 35 ]. In the isolates where virulence genes were found in combination, stx2-st , sx1-st, stx1-stx2 , and lt-st represented the dominant combinations.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In our study, stx1, stx2, and st VGs were more frequent than eae , hly , aatA , and lt . In another report, however, stx1 and eae were found at a higher rate than st and stx2 [ 35 ]. In the isolates where virulence genes were found in combination, stx2-st , sx1-st, stx1-stx2 , and lt-st represented the dominant combinations.…”
Section: Discussionmentioning
confidence: 91%
“…Virulence genes are extensively used in determining E. coli pathotypes and have been found in multiple combinations [ 34 , 35 ]. In our study, stx1, stx2, and st VGs were more frequent than eae , hly , aatA , and lt .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, we recently found that camels affected by diarrhea expressed a higher prevalence of fimbriae F17 than clinically healthy camels (46.5% vs. 14.5%) [ 9 ]. Several other studies also reported the association of this adhesin with diarrhea and/or sepsis observed in newborn alpacas [ 10 ], calves [ 11 , 12 , 13 , 14 ], lambs [ 5 , 15 ] and horses [ 16 ]. All this justifies the growing interest in this virulence factor as a therapeutic target and for the design of diagnostic tools such as ELISA and biosensing platforms.…”
Section: Introductionmentioning
confidence: 95%
“…The fimbrial adhesins, F5 [9], F17 [10], F18 [11], and F41 [12] are associated with ETEC mainly in young animals. E. coli F17, one of the main subtypes of ETEC, has been reported as the major pathogen associated with ETEC-related diarrhea worldwide, responsible for high morbidity and mortality [13][14][15]. The growing prevalence of E. coli F17 has renewed the sense of urgency for E. coli F17 research.…”
Section: Introductionmentioning
confidence: 99%